Spoof surface plasmon polaritons-based feeder for a dielectric rod antenna at microwave frequencies - Ismail, Mohd Muzafar; Al Gburi, Ahmed Jamal Abdullah; Chaparala, Rishitej; Imamvali, Shaik; Tupakula, Sreenivasulu; Prakash, Krishna; Bansal, Shonak (Electromagnetics Academy, 2024)
This work explores the potential of spoof surface plasmon polaritons (SSPPs) for effectively feeding high-frequency antennas operating in the extremely high-frequency (EHF) range. An innovative approach is introduced in this study to utilize SSPP to feed a dielectric rod antenna. The design incorporates a straightforward dielectric rod antenna fabricated using FR-4 material with a relative permittivity of 4.3. Compared to conventional tapered dielectric rod antennas and their corresponding feeding configurations, this design presents the potential benefit of achieving an improved gain of up to 16.85 dBi using a specific antenna length of 7.6λ0. Through careful design optimization, we achieved impedance matching and directional radiation characteristics at a frequency of 7.3 GHz. To validate our design and assess its performance, we conducted simulations using the CST Microwave Studio. This study aims to demonstrate the effectiveness and practicality of the proposed dielectric rod antenna with an SSPP feed.